Cooperative Localization Algorithm Based on Hybrid Topology Architecture for Multiple Mobile Robot System - Sun, Qian; Tian, Yu; Diao, Ming (IEEE internet of things journal, 2018)
With the development of robotics, the multiple mobile robot system (MMRS) has been an attention-getting subject in recent years and has been widely used in military, civilian and other fields. Cooperative localization is the key technology of the MMRS. And observability analysis for MMRS and nonlinear problem are the foremost problems to cooperative localization. In order to enhance the accuracy of cooperative localization for MMRS, a novel cooperative localization algorithm based on hybrid topology architecture under the framework of extended Kalman filter (EKF) is proposed in this paper. In this novel algorithm, a hybrid topology architecture based on the relative position measurement graph method is adopted to enhance the usage efficiency of observations, improving the cooperative localization accuracy. Meanwhile, EKF is used in this novel cooperative localization algorithm to solve the nonlinearity of the MMRS. Finally, a real dataset is used to verify the availability and superiority of this novel algorithm.